Dehesas as high nature value farming systems: a social-ecological synthesis of drivers, pressures, state, impacts, and responses - Tobias Plieninger (Resilience Alliance, 2021)
Dehesas and montados are Mediterranean agroforestry systems characterized by scattered oak trees with an understory grazed extensively by livestock and, in some cases, periodically cropped. A long history of traditional management practices has created an open woodland widely recognized for rich biodiversity and multiple ecosystem services. Concerns about challenges to their long-term viability have motivated many disparate scientific studies in recent decades. We provide a synthesis of this growing body of international literature, focusing on the links between land use and management practices, biodiversity, and policy, from a "high nature value farming systems" perspective. The present review comprises 128 empirical studies carried out in Spain and Portugal. Conservation trends were assessed according to categories adapted from the DPSIR (Drivers - Pressures - State - Impacts - Responses) framework. Socio-cultural factors, economic dynamics, and agricultural policies were found to be key drivers of change, resulting in intensification of livestock production and land use simplification, among other effects. Insufficient tree regeneration and a broad range of other factors were identified as pressures that have often negative impacts on biodiversity and ecosystem services, moving the system away from its archetypical ecological state. A variety of management and policy responses were suggested, ranging from specific conservation techniques to landscape-level initiatives. Ecosystem components and management practices were typically studied separately, and mainly from an ecological science perspective, while inter- and transdisciplinary approaches including examination of the role of people were less common. This points to a need to move from single-topic to landscape-level approaches with a broader integration of different disciplines and perspectives.